Предмет: Алгебра, автор: berdnikovaolesya777

упростить выражение (4х-3)2х-(2х+1)(3х-2)2х при х=0,7​

Ответы

Автор ответа: evgenrubalko11
1

(4x - 3) \times 2x - (2x + 1)(3x - 2) \times 2x = 8 {x}^{2}  - 6x - (6 {x}^{2}  - 4x + 3x - 2) \times 2x = 8 {x}^{2}  - 6x -(12 {x}^{3}  - 8 {x}^{2}  + 6 {x}^{2}  - 4x) = 8 {x}^{2}  - 6x - (12 {x}^{3}  - 2 {x}^{2}  - 4x) = 8 {x}^{2}  - 6x -12 {x}^{3}   + 2 {x}^{2}  + 4x =  - 12 {x}^{3}  + 10 {x}^{2}  - 2x =  - 2x(6 {x}^{2}  - 5x + 1)

при х=0,7

 - 2 \times 0.7(6 \times  {0.7}^{2}  - 5 \times 0.7  + 1) =  - 1.4(2.94 - 3.5 - 1) =  - 1.4 \times 0.44 =  - 0.616

Похожие вопросы
Предмет: Математика, автор: Egor787